Unveiling Planetary Systems in Solar Twins with High-Precision Radial Velocity - Santos, Thiago Ferreira dos (2023)
The search for exoplanets has witnessed significant growth in recent years with the dawn of new instruments and precise data analysis techniques. Recent observations suggest that cold giant planets are likely to form around stars possessing metallicity levels comparable to those of the Sun, while low-mass, potentially habitable planets may be common around stars that host cold Jupiter-like planets. This study presents the detection of 16 exoplanetary systems from the analysis of high-precision radial velocity time series data from the ESO/HARPS spectrograph, concentrating on solar twin stars as part of the Solar Twin Planet Search programme. We examined correlations between magnetic stellar activity indicators and radial velocity measurements, alongside timing variations, to detect any potential exoplanetary candidates\' modulations. Then, we employed Keplerian models and quasi-periodic Gaussian process regression in some cases, to probe the physical and orbital features of the candidates found. Our results offer significant insights into the formation and evolution of planetary systems around solar twin stars, uncovering planetary engulfment phenomena and the existence of outer companions that may contribute to the dynamic evolution of mainly inner ice giant exoplanets. Our findings include several Neptune-like and Jupiter analogues, laying the ground with a catalogue of targets to be observed by the next generation of ground- and space-based telescopes seeking Earth-analogue exoplanets.